ANALISIS PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, PARTISIPASI PENGANGGARAN DAN PENGAWASAN TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA - Djoko Kristianto, Dwi Sapartiningsih, Suharno & (Universitas Slamet Riyadi, 2018)
The purpose of this research is to analyze the significance of the influence of the competence of human resources, utilization of information technology, budgeting and monitoring participation against the accountability of the management of the village Fund at the Government Village in district Sumberlawang Kabupaten Sragen. Populations and samples in this study are all parties involved in the preparation of ABBDes at the Government village in sub-district of Sumberlawang Sragen district of 77 people, so this research is the study of the census. Methods of data collection were used: questionnaire and documentation. Technique of data analysis used the test of validity, reliability test, test the assumptions of classical, and multiple linear regression analysis, t-test, F-test and coefficient of determination. The research results obtained the conclusion that there is a significant positive influence on the competence of the human resources management accountability against the village Fund. There is a significant positive influence on the utilization of information technology fund management accountability towards the village. There is a significant positive influence on participation in budgeting management accountability against the village Fund. There is a significant positive influence on the supervision of fund management accountability towards the village.Keywords: competence of human resources, utilization of information technology, budgeting participation, oversight, accountability of managing the village Fund.